2011
DOI: 10.3928/01484834-20110616-02
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity Pyramid: An Organizational Model to Structure Diversity Recruitment and Retention in Nursing Programs

Abstract: The literature on increasing the diversity of individuals who enter and practice the nursing profession comes with sound argument, yet we have seen only modest gains in diversification over the past 10 years. This article addresses how to develop a sustainable program to increase the recruitment and retention of underrepresented students. The diversity pyramid is suggested as a conceptual planning model for increasing diversity that is matched to an institution and its resources. The foundation of the pyramid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Different strategies to assist candidates in identifying nursing as a possible career are documented (Roberts & Ward‐Smith, ) based on the individual needs of the potential candidates (Rosenberg & O'Rourke, ). However, little evidence is available on the effectiveness of different recruitment strategies (Law & Arthur, ) given that a more profound understanding of the career decision‐making process has not been documented (Mooney et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Different strategies to assist candidates in identifying nursing as a possible career are documented (Roberts & Ward‐Smith, ) based on the individual needs of the potential candidates (Rosenberg & O'Rourke, ). However, little evidence is available on the effectiveness of different recruitment strategies (Law & Arthur, ) given that a more profound understanding of the career decision‐making process has not been documented (Mooney et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Recruitment strategies might be effective if they are based on the needs of the society (e.g. involve minorities, diversifying the workforce), on available resources (human, financial and organizational), on analysis of the labour market (Rosenberg & O'Rourke ) and on the reasons why students at university matriculation do not choose a nursing degree (Cho et al. ; Miers et al.…”
Section: Introductionmentioning
confidence: 99%
“…Recruitment strategies might be effective if they are based on the needs of the society (e.g. involve minorities, diversifying the workforce), on available resources (human, financial and organizational), on analysis of the labour market (Rosenberg & O'Rourke 2011) and on the reasons why students at university matriculation do not choose a nursing degree (Cho et al 2010;Miers et al 2007). Focusing on the latter (Cho et al 2010) is crucial not only for understanding why nursing is unattractive but also for understanding the data on which this unattractiveness is based.…”
Section: Introductionmentioning
confidence: 99%
“…Nursing leadership for this initiative emphasized the invaluable role of institutional commitment in ensuring successful recruitment and success in nursing programs. 12 Minority nurse faculty underrepresentation is yet another concern. Recent findings revealed that 12.6% of full-time nursing school faculty come from minority backgrounds, and approximately 6.2% are male.…”
Section: Diversity In the Nursing Workforcementioning
confidence: 99%